Essentials of biostatistics in public health - Sullivan, Lisa M. (Lisa Marie), 1961- (Essential public health, 2023)
"Essentials of Biostatistics in Public Health, Fourth Edition provides a fundamental and engaging background for students learning to apply and appropriately interpret biostatistics applications in the field of public health. Many examples are drawn directly from the author's remarkable clinical experiences with the renowned Framingham Heart Study, making this text practical, interesting, and accessible for those with little mathematical background. The examples are real, relevant, and manageable in size so that students can easily focus on applications rather than become overwhelmed by computations.The Fourth Edition has been thoroughly updated, and now offers a new chapter on career opportunities and new case studies in each chapter focused on COVID-19. This edition will also include free access to JMP Student Edition Software, which is an easy-to-use version of SAS' statistical discovery software and is well-suited to for introductory or intermediate statistics courses. Key Features: Updated "in the news" features at the start of each chapter. Additional problems for students to test their knowledge. Revised instructor resources with suggestions for teaching biostatistics online. Updated Excel Workbook--included in the ebook--provides hands-on experience with statistical computing using Microsoft Excel. New JMP Student Edition Software--included for free download with purchase of the book or eBook--provides a streamlined, easy-to-use version of SAS' statistical discovery software. New accompanying JMP workbook--included in the eBook--provides exercises and examples of how to use JMP modeling and computing biostatistics"--